Sosialisasi, Simulasi Kebakaran Dan Pendampingan Budaya K3 Untuk Usia Dini Di SD “Rumah Sekolah Cendikia” Kel.Paccinongan Kec.Somba Opu Kabupaten Gowa - Irwan Setiawan Muthalib (Faculty of Engineering UNHAS, 2020)
K3 implementation is important and the responsibility of all parties, not only in the world of work but also in the world of Education. The first introduction to OSH at an early age (Irwan S.2017). Law No. 1 of 1970 is the basis of the first law stipulated by the government and also an understanding of K3. All parties involved are obliged to play an active role in accordance with their functions and authority and make K3 a part of the activity culture in each activity, so as to prevent accidents and illnesses caused by activities. For this reason, the purpose of this activity is to provide information and improve insight to children at the elementary school level to recognize potential hazards that can arise in the surrounding environment such as at home, at school and on the streets, so that accidents and diseases due to certain activities can be reduced or prevented as early as possible. Some of the targets to be achieved in this activity are to increase partners' knowledge of the potential danger of accidents at home, at school, and on the road and increase partner knowledge about the first important things to do if an accident occurs at home, at school and on the road.